2011
DOI: 10.1027/1614-0001/a000032
|View full text |Cite
|
Sign up to set email alerts
|

Procedural and Distributive Justice Beliefs for Self and Others

Abstract: Both theory and research suggest that beliefs about justice for the self are distinct from beliefs about justice for others. Self-other differences, however, have not yet intersected with research on procedural and distributive justice. We examined the psychometrics and validity of a proposed four-dimensional measure of procedural and distributive justice beliefs for self and others. Participants from three samples (total N = 1463) completed dispositional measures of beliefs about fair outcomes (distributive j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 49 publications
4
71
0
Order By: Relevance
“…A multiple regression analysis revealed that although the two self subscales (distributive and procedural) were significantly predictive of life satisfaction, the two other (distributive and procedural) subscales were not (see Table 3). These results are consistent with the finding by Lucas et al [2].…”
Section: Correlation Between Satisfaction With Life and Belief In A Jsupporting
confidence: 94%
See 3 more Smart Citations
“…A multiple regression analysis revealed that although the two self subscales (distributive and procedural) were significantly predictive of life satisfaction, the two other (distributive and procedural) subscales were not (see Table 3). These results are consistent with the finding by Lucas et al [2].…”
Section: Correlation Between Satisfaction With Life and Belief In A Jsupporting
confidence: 94%
“…Lucas et al [2] found the two self-justice subscales to be more strongly correlated with life satisfaction than the two other subscales. They also found the two self-justice subscales, but not the two other subscales, were predictive of life satisfaction in a multiple regression analysis.…”
Section: The Relationship Between Just World Beliefs and Life Satisfamentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, children at 9 were able to use procedures to hide their intentions for self-interest maximization ( Shaw et al, 2014 ). The manipulability of procedural justice perhaps explains why people’s belief in distributive justice rather than procedural justice at an individual level is more predictive of their self-rated health ( Lucas et al, 2011 ). Therefore, procedural justice is not entirely the same as distributional justice in terms of uncertainty and manipulability, suggesting the importance of investigating children’s development in the area of procedural justice.…”
Section: Introductionmentioning
confidence: 99%